2019
DOI: 10.22159/ijap.2019.v11s1.156
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Identified Javanese Turmeric Ethanol Extract for the Inhibition of Biofilm Formation by Streptococcus Mutans and Porphyromonas Gingivalis

Abstract: Objective: To study the effectiveness of identified Javanese turmeric ethanol extract (IJTEE) against single and combined biofilm formation byStreptococcus mutans and Porphyromonas gingivalis.Methods: S. mutans ATCC 25175 and P. gingivalis ATCC 33277 were tested for the minimum inhibitory concentration (MIC) and minimum bactericidalconcentration (MBC) of IJTEE using microdilution technique. The inhibition of biofilm formation by IJTEE was analyzed using crystal violet assay.Results: MIC and MBC of IJTEE for S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Our studies have shown that the effectiveness of C. xanthorrhiza ethanol extract against Gram-positive bacteria was superior compared with its effect against Gram-negative bacteria. In addition, the efficacy of C. xanthorrhiza extract and XNT against Gram-positive bacteria is comparable to CHX [48,49,52].…”
Section: Antibacterial and Antibiofilm Activity 41 Antibacterialmentioning
confidence: 93%
See 1 more Smart Citation
“…Our studies have shown that the effectiveness of C. xanthorrhiza ethanol extract against Gram-positive bacteria was superior compared with its effect against Gram-negative bacteria. In addition, the efficacy of C. xanthorrhiza extract and XNT against Gram-positive bacteria is comparable to CHX [48,49,52].…”
Section: Antibacterial and Antibiofilm Activity 41 Antibacterialmentioning
confidence: 93%
“…Medicinal plant's extract from Acacia arabica, Tamarix aphylla L., and Melia azadirachta L. showed evidence of reducing oral biofilm formation and cleaning the well-developed oral biofilm [45]. Medicinal plant from South East Asia, C. xanthorrhiza Roxb., has also been proven through several studies to have eradication and inhibition effects against oral bacteria and candida biofilm [23,[46][47][48][49][50][51][52][53].…”
Section: Current Treatment and Challenges Using Chx And Other Antibac...mentioning
confidence: 99%